Impact of gender, work, and clinical presentation on diagnostic delay in Italian patients with primary ankylosing spondylitis. Issue 2 (February 2016) - Bandinelli, F.; Salvadorini, G.; Sedie, A.; Riente, L.; Bombardieri, S.; Matucci-Cerinic, M.
Abstract The variability of demographic, social, genetic, and clinical factors might influence the time between the onset of symptoms and the diagnosis [diagnostic delay (DD)] of ankylosing spondylitis (AS) in different geographic areas. Different clinical manifestations in men and women affected by AS might indicate a possible role of gender in DD. The aim of the present study was to investigate the influence of demographic, social, genetic, and clinical factors on DD and the differences of DD between men and women related to the presence of different demographic, social, clinical, and genetic parameters in an Italian cohort of primary AS patients. A total of 135 Italian primary AS patients (45 female and 90 male, 27.9 ± 0.89 years old at onset) were studied. The DD, gender, education and work (manual or non-manual) levels, and type of first clinical presentation (inflammatory back pain, arthritis, enthesitis) at onset, family history of AS, and HLA B27 presence were analyzed. The DD (8.744 mean ±0.6869) was significantly higher in men (p  = 0.0023), in axial presentation (p  = 0.0021), and in manual work (even if with low significance, p  = 0.047). The lower DD in women in comparison to that in men was likely related to higher education (p  = 0.0045) and work (p  = 0.0186) levels, peripheral involvement (p  = 0.0009), and HLA B27 positivity (p  = 0.0231). DD was higher in AS patients: male, employed in manual jobs, and with axial symptoms at onset. In men, DD seemed to be negatively influenced by lower level of education and work, axial clinical presentation, and HLA B27.